Characterizing femoroacetabular impingement in professional Nordic Skiers - Vasavada, K.; Ross, K. A.; Lott, A.; Shankar, D.; Marulanda, D.; Mojica, E. S.; Carter, C. W.; Borowski, L.; Gonzalez-Lomas, G. (The Physician and Sportsmedicine, 2023)
Objective Studies have shown a high prevalence of femoroacetabular impingement (FAI) among elite athletes yet there is a paucity of data on FAI in Nordic skiers. The purpose of this study was to determine the prevalence of radiographic FAI in professional Nordic Combined Skiers and Ski jumpers compared to controls and assess functional outcomes including hip range of motion (ROM) and pain in patients with radiographic evidence of FAI compared to those without it.